(untitled) (European Journal of Teaching and Education, 2023)
Guided by Marxist theory and Bourdieu’s theory of capital, this paper explores the impact of the marketisation of education on society by analysing the case of Hengshui Middle School in China in terms of its expansion in the education market. The paper finds that the impact of the marketisation of education on society is the pro and con side of a coin, as it optimises the allocation of educational resources in society to a certain extent while also having a negative impact on social justice and equity; in addition to this, the paper also compares Marxian and Bourdieu’s theories while elaborating on them, finding that Bourdieu’s theory is able to embody more insights in explaining educational equity.